Quantitative comparison of measurements of urgent care service quality. Issue 1 (2nd January 2016) - Qin, Hong; Prybutok, Victor; Prybutok, Gayle
ABSTRACT: Service quality and patient satisfaction are essential to health care organization success. Parasuraman, Zeithaml, and Berry introduced SERVQUAL, a prominent service quality measure not yet applied to urgent care. We develop an instrument to measure perceived service quality and identify the determinants of patient satisfaction/ behavioral intentions. We examine the relationships among perceived service quality, patient satisfaction and behavioral intentions, and demonstrate that urgent care service quality is not equivalent using measures of perceptions only, differences of expectations minus perceptions, ratio of perceptions to expectations, and the log of the ratio. Perceptions provide the best measure of urgent care service quality.